Evaluation of an Adolescent Development Program for Girls in Tanzania - Buehren, Niklas; Goldstein, Markus; Gulesci, Selim; Sulaiman, Munshi; Yam, Venus (World Bank, Washington, DC, 2017)
This paper evaluates a program targeted to adolescent girls in Tanzania that aims to empower them economically as well as socially. The program was found to be highly successful in Uganda in terms of economic, health, and social outcomes. In contrast, this evaluation finds that the program did not have any notable effect on most of these outcomes in the Tanzanian setting. The evaluation also measures the impact of the program with and without microcredit services. The findings show that the addition of microcredit improves the take-up of the program and savings of the participants. The paper explores programmatic implementation information that helps explain the marked difference in outcomes between Uganda and Tanzania. This research shows that layering additional microfinance services onto an adolescent development program can be an effective tool to attain greater inclusion of youth in financial services, and brings out important issues of the generalizability of the research findings.